2016
DOI: 10.1631/jzus.b1500264
|View full text |Cite
|
Sign up to set email alerts
|

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus

Abstract: Abstract:The antioxidant activities and total phenolic content of fermented Salvia miltiorrhiza with fungus Geomyces luteus were investigated. The results revealed that G. luteus fermentation could significantly improve the antioxidant activity and total phenolic content of S. miltiorrhiza. The main antioxidant constituents were characterized by spectroscopic analysis as salvianolic acids. High-performance liquid chromatography (HPLC) quantification also showed the enhanced content of salvianolic acid B after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…have antioxidant activities (Shi, Sun, Sun, & Zhang, ), such as water‐insoluble diterpene quinones and water‐soluble phenolic acids. In particular, water‐soluble phenolic acids possess significant antioxidant activity (Xing et al, ). From the results of PCA for HPLC fingerprinting and quantitation of 10 constituents, SSM and NSSM were separated into two classes, which might lead to differences in their efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…have antioxidant activities (Shi, Sun, Sun, & Zhang, ), such as water‐insoluble diterpene quinones and water‐soluble phenolic acids. In particular, water‐soluble phenolic acids possess significant antioxidant activity (Xing et al, ). From the results of PCA for HPLC fingerprinting and quantitation of 10 constituents, SSM and NSSM were separated into two classes, which might lead to differences in their efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…have antioxidant activities (Shi, Sun, Sun, & Zhang, 2016), such as water-insoluble diterpene quinones and water-soluble phenolic acids. In particular, water-soluble phenolic acids possess significant antioxidant activity (Xing et al, 2016 ity. In brief, the above methods gave similar results that the antioxidant activity of SSM was significantly higher than that of NSSM (p < 0.01) which can also be obtained visually from Figure 7.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies have reported that some phenolic compounds including flavonoids, such as kaempferol, parulerin, luteolin and epigallocatechin, have inhibitory effects on tyrosinase (Kim and Uyama, 2005;Huang et al, 2013). Furthermore, many have studied a fermentation technique of bioactive flavonoids to improve their bioactivity (Xing et al, 2016). This study showed that the extracts fermented by L. plantarum had greater antioxidant and tyrosinase inhibitory effects than the non-fermented extract, suggesting that the fermentation of Inula extracts can be applied to the industrial development of both functional foods and cosmetics.…”
Section: 5mentioning
confidence: 99%
“…For example, the oral administration of probiotic-fermented red ginseng to diabetic mice significantly decreased the blood glucose levels by approximately 62.5% in the fasting state and induced a significant increase in glucose tolerance by approximately 10.2% compared to the control mice [16]. In another study, Salvia miltiorrhizae fermented by Geomyces luteus was shown to significantly improve its antioxidant activity and total phenolic content [17].…”
Section: Introductionmentioning
confidence: 95%